2014
DOI: 10.4103/1119-3077.130246
|View full text |Cite
|
Sign up to set email alerts
|

On the use of drains in orthopedic and trauma

Abstract: Postoperative wound drains make for neat postoperative period with less tissue swelling. There was no statistically significant differences between the drained and undrained wounds in terms of infection rates, haematoma or seroma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Our findings support the evidence that drain use in orthopaedic wounds is associated with a higher risk of surgical site infection [4,18]. However, prior literature is equivocal with several studies demonstrating no difference or even decreased rates of infection with drain use [10,19,20]. Multi-center studies with standardized drain procedures would clarify the effect of prophylactic drain use on the infection rate in orthopaedic surgical wounds.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings support the evidence that drain use in orthopaedic wounds is associated with a higher risk of surgical site infection [4,18]. However, prior literature is equivocal with several studies demonstrating no difference or even decreased rates of infection with drain use [10,19,20]. Multi-center studies with standardized drain procedures would clarify the effect of prophylactic drain use on the infection rate in orthopaedic surgical wounds.…”
Section: Discussionsupporting
confidence: 86%
“…Lowering healthcare associated costs is an ongoing objective of many low-and middle-income countries (LMICs), and the use of drains in orthopaedic surgery is associated with increased cost [4,30]. Khanal et al reported that cost of treatment, inclusive of drain use, was higher than other routine orthopaedic cases [19], and the average drain costs in similar studies have been cited as 25-30 USD [4,10]. Although drain cost is variable, it adds to the financial burden of healthcare for many patients in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placement of post-operative incisional drains following spinal surgery is a controversial topic, and its utilization has varied over time (1). Periprosthetic closed drains are widely utilized in other surgical subspecialties (2)(3)(4)(5)(6)(7)(8)(9) with objective of minimizing hematoma formation and surgical site infections (SSI). In spinal surgery, the use of closed, high or low pressure drain alternatives are believed to attenuate persistent wound drainage, infection, and hematoma formation in the post-operative setting (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…There may be areas of ecchymosis also. Drains delay mobilization, could get dislodged and complicates nursing [14][15][16][17][18][19][20][21] . Other studies have shown similar findings with regard to blood loss.…”
Section: Introductionmentioning
confidence: 99%